Demographic influence on COVID-19 reinfection at the Integrated Laboratory of Syarif Hidayatullah State Islamic University Jakarta - Fiena Febriyana; Suwarsono, Erike A. (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2025)
Background: COVID-19 can reinfect the same person, or it can be called reinfection. Reinfection that occurs has a slightly higher severity level, characterised by the need for ventilation and intensive care in the ICU, than the first infection. This study aimed to determine the influence of demographics on COVID-19 reinfection cases in the Integrated Laboratory of the Faculty of Medicine, Syarif Hidayatullah State Islamic University Jakarta, in 2020-2022. Methods: The study was an observational analytical study using a cross-sectional design conducted on patients in the Integrated Laboratory of the Faculty of Medicine, Syarif Hidayatullah State Islamic University Jakarta, who were selected by consecutive sampling. Results: The study aims to understand the relationship between gender, age, occupation, blood type, and source of sample with cases of COVID-19 reinfection. This study collected 396 samples. It was found that the majority of samples had the characteristics of women (57.8%), young adults (35.9%), unknown occupation (45.7%), unknown blood type (39.4%), hospital patients (90.2%), and experienced reinfection (31.8%). The results of the bivariate analysis showed a significant relationship between gender and age with cases of COVID-19 reinfection. Conclusions: A significant relationship was found between gender and age with cases of COVID-19 reinfection at the Integrated Laboratory of the Faculty of Medicine, Syarif Hidayatullah State Islamic University Jakarta.